Association of Cardiovascular Hyperreactivity and Obesity between Sedentary and Active Individuals - Milagros Lisset León Regal; Lázaro Hermes González Otero; Luis Alberto Mass Sosa; Jacqueline Zamora Galindo; Lucía Baños Leyva; Claudia González Martínez (Revista Finlay)
Background: there are several studies that show a relationship between cardiovascular hyperreactivity and some cardiovascular risk factors, but it is necessary to continue showing this relationship. Objective: to determine the association of cardiovascular hyperreactivity and obesity between sedentary and active individuals in Cienfuegos. Methods: a descriptive, cross-sectional and correlational study was carried out in a universe of 80 individuals between 18 and 30 years of age in the Cienfuegos municipality, during 2020. The variables analyzed were: age, sex, skin color, level of sedentary lifestyle, pressure baseline blood pressure with the sustained weight test, body mass index and abdominal waist. Pearson's Chi Square was used to describe the association of the study variables between sedentary and active individuals, as well as the T test for the comparison of means. Significance level p˂0.05. The results were expressed in charts. Results: ages 18-24 years old and white skin color predominated. 76.3 % have a sedentary lifestyle over assets. 65.6 % of the sedentary were female. In the anthropometric tests, more than 30 % were overweight-obese and 20 % had altered abdominal waist, for both the condition of being sedentary coexisted. The sedentary subjects presented mean values of the hemodynamic variables higher than the active subjects. 73.8 % of the sedentary subjects were cardiovascular hyperreactive, as opposed to the normoreactive cardiovascular state that was present in 94.7 % of the active subjects. Conclusions: the condition of sedentary lifestyle increases the values of the hemodynamic and anthropometric variables studied.